PP44 Impact of negative aspects of close relationships on cognitive ageing, the dark side of social relationships. (2nd September 2014) - Liao, J; Head, J; Kumari, M; Stansfeld, S; Singh-Manoux, A; Brunner, EJ
Abstract : Background: The extent to which social relationships influence cognitive ageing is unclear. This study investigates the impact of mid-lif quality of close relationships on cognitive decline, using multilevel modelling. Methods: Whitehall II study participants (n = 6495, aged 45–69 at baseline) provided cognitive assessments (executive function and memory) three times over 10 years. The quality of close relationships was assessed by the Close Persons Questionnaire. Results: Higher levels of adverse close relationships in mid-life were related to lower concurrent memory (-0.07; 95% CI: -0.12, -0.02 SD) and accelerated 10-year decline in executive function (-0.04; 95% CI: -0.07, -0.01 SD). Participants reporting higher cumulative negative aspects of close relationships experienced greater decline in executive function (-0.04; 95% CI: -0.07, -0.01 SD). Longitudinal analysis found no evidence of reverse causality. Conclusion: Adverse close relationships predict relatively rapid cognitive ageing. This study highlights the importance of differentiating aspects of social relationships to evaluate their unique health effects.